2021
DOI: 10.3390/ijerph18147413
|View full text |Cite
|
Sign up to set email alerts
|

Going “Up” to Move Forward: S-1 Bifactor Models and the Study of Neurocognitive Abilities in Psychopathology

Abstract: Recently, structural models of psychopathology, that address the diagnostic stability and comorbidity issues of the traditional nosological approach, have dominated much of the psychopathology literature. Structural approaches have given rise to the p-factor, which is claimed to reflect an individual’s propensity toward all common psychopathological symptoms. Neurocognitive abilities are argued to be important to the development and maintenance of a wide range of disorders, and have been suggested as an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
(114 reference statements)
0
13
0
Order By: Relevance
“…Traditional nosological approaches to the diagnosis of mental disorder, which use tools such as the DSM, have resulted in high levels of comorbidity and poor diagnostic stability, e.g., [14,15], making the study of any single psychopathological disorder difficult [13]. Further, the overlapping symptoms present between different disorders, as well as the ability for two people to be diagnosed with the same disorder and having no, or very few, common symptoms [16,17], means that finding particular collections of neurocognitive deficits fundamental to any particular disorder is unlikely [9,13,18].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Traditional nosological approaches to the diagnosis of mental disorder, which use tools such as the DSM, have resulted in high levels of comorbidity and poor diagnostic stability, e.g., [14,15], making the study of any single psychopathological disorder difficult [13]. Further, the overlapping symptoms present between different disorders, as well as the ability for two people to be diagnosed with the same disorder and having no, or very few, common symptoms [16,17], means that finding particular collections of neurocognitive deficits fundamental to any particular disorder is unlikely [9,13,18].…”
Section: Introductionmentioning
confidence: 99%
“…As structural models of psychopathology do not create diagnostic categories and instead measure dimensionally, it has been suggested that structural models will improve our ability to find more reliable patterns of risk factors and outcomes associated with psychopathology [13,18,20]. While it is important to note that there is a lack of consensus on the substantive interpretation of the factors of psychopathology, in particular the p-factor, and their applications to subgroups of a population, for further detail see [18,22,23], struc-tural models of psychopathology offer a useful framework for examining the associations between neurocognitive abilities and psychopathology [13]. Previously, we suggested that it may be possible to find, at a population level, patterns of association between neurocognition and the factors of psychopathology that help explain the differentiation between the factors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations